Regulation of Exopolysaccharide Production by Lactococcus lactis subsp. cremoris by the Sugar Source - Looijesteijn, Petronella J. (American Society for Microbiology, 1999)
Lactococcus lactis produced more exopolysaccharide (EPS) on glucose than on fructose as the sugar substrate, although the transcription level of the eps gene cluster was independent of the sugar source. A major difference between cells grown on the two substrates was the capacity to produce sugar nucleotides, the EPS precursors. However, the activities of the enzymes required for the synthesis of nucleotide sugars were not changed upon growth on different sugars. The activity of fructosebisphosphatase (FBPase) was by far the lowest of the enzymes involved in precursor formation under all conditions. FBPase catalyzes the conversion of fructose-1,6-diphosphate into fructose-6-phosphate, which is an essential step in the biosynthesis of sugar nucleotides from fructose but not from glucose. By overexpression of the fbp gene, which resulted in increased EPS synthesis on fructose, it was proven that the low activity of FBPase is indeed limiting not only for EPS production but also for growth on fructose as a sugar source.